2020
DOI: 10.1186/s12913-020-05583-x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of community based health insurance uptake and associated factors among urban residents of Oromia regional state, Oromia, Ethiopia, a cross-sectional study

Abstract: Background Globally, Millions of people cannot use health services because of the fear of payment for the service at the time of service delivery. From the agenda of transformation and the current situation of urbanization as well as to ensure universal health coverage implementing this program to the urban resident is mandatory. The aim of this study is to assess the willingness of community-based health insurance (CBHI) uptake and associated factors among urban residents of Oromia regional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
1
11
2
Order By: Relevance
“…Based on this, 89.8% of the household heads in the study area were willing to pay community based health insurance. The study nding is in line with the was done in selected districts in Jimma Zone, South west Ethiopia, 90 % (18).the nding higher than the studies was done in the area Oromiya region, 83.9% and north central Nigeria, 87% (3,19).This study revealed that, the mean amount of money household heads willing to pay was 334.02 ETB (±142.608) per house hold per annual and the median amount was 280 birr. This greater than the study was carried out in the rural community of Fogera district, the mean amount of money household heads willing to pay was 187birr (+21) per house hold per annual and the median amount was 200 birr(1).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on this, 89.8% of the household heads in the study area were willing to pay community based health insurance. The study nding is in line with the was done in selected districts in Jimma Zone, South west Ethiopia, 90 % (18).the nding higher than the studies was done in the area Oromiya region, 83.9% and north central Nigeria, 87% (3,19).This study revealed that, the mean amount of money household heads willing to pay was 334.02 ETB (±142.608) per house hold per annual and the median amount was 280 birr. This greater than the study was carried out in the rural community of Fogera district, the mean amount of money household heads willing to pay was 187birr (+21) per house hold per annual and the median amount was 200 birr(1).…”
Section: Discussionsupporting
confidence: 86%
“…and north central Nigeria, 87% (3,19).This study revealed that, the mean amount of money household heads willing to pay was 334.02 ETB (±142.608) per house hold per annual and the median amount was 280 birr. This greater than the study was carried out in the rural community of Fogera district, the mean amount of money household heads willing to pay was 187birr (+21) per house hold per annual and the median amount was 200 birr(1).…”
Section: Discussionmentioning
confidence: 71%
“…This low level of willingness could result in low CBHI utilization and a high dropout rate and which in turn affect the 2035 country plan of achieving universal health coverage [21]. Besides, there was regional variation among studies regarding willingness to join the program and associated factors [33][34][35][36][37][38][39][40][41]. This study was intended to examine willingness towards the community-based health insurance and associated factors in south wollo zone northeast Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of OOP accounted for 34% of the total health-care expenditures in Ethiopia. As a result, a significant number of households were exposed to financial hardship for many years [5][6][7]. However, to bring the cost of catastrophic health care to insignificant levels, the World Health Organization (WHO) recommended the OOP payment at a level of less than 15 to 20% of the total health-care expenditure.…”
Section: Introductionmentioning
confidence: 99%